21. Efficacy and Safety of Maribavir as a Rescue Treatment for Investigator Assigned Therapy in Transplant Recipients With Refractory or Resistant Cytomegalovirus Infections in the SOLSTICE Study: Phase 3 Trial Results. (4th December 2021) - Pereira, Marcus; Cervera, Carlos; Kotton, Camille; Kotton, Camille; Sasadeusz, Joseph; Wu, Jingyang; Fournier, Martha
Abstract: Background: Refractory or resistant (R/R) cytomegalovirus (CMV) infection after hematopoietic cell transplant (HCT) and solid organ transplant (SOT) cause serious, potentially fatal complications; therapeutic options are limited. In a Phase 3 study (NCT02931539), maribavir (MBV) was superior to investigator-assigned therapy (IAT; val/ganciclovir, foscarnet, cidofovir) for CMV clearance (Wk 8) and clearance plus symptom control (Wk 8 through Wk 16) in HCT/SOT recipients with R/R CMV infections. Here we present further study results on efficacy and safety of MBV in the rescue arm. Methods: Patients (pts) were stratified and randomized 2:1 to MBV (400 mg/bid) or IAT for 8-wk treatment then 12-wk follow-up. After minimum 3 wks' treatment, pts in the IAT group meeting criteria (worsening/lack of improvement of CMV infection or failure to achieve viremia clearance plus IAT intolerance) could enter a MBV rescue arm (8-wk treatment, 12-wk follow-up). In the rescue arm, efficacy was evaluated by confirmed CMV viremia clearance (plasma CMV DNA < 137 IU/mL in 2 consecutive tests ≥ 5 days apart) at end of Wk 8 and confirmed clearance with symptom control at Wk 8 through Wk 16. Safety was assessed. Results: A total of 352 pts were randomized (MBV: 235, IAT: 117, randomized set). Confirmed CMV viremia clearance at Wk 8 was achieved in 131 (55.7%) and 28 (23.9%) pts, respectively, in the randomized set. Having met criteria, 22 (18.8%) pts entered the MBV rescue arm; at entry, 6 (27.3%) pts had developed neutropenia and 9 (40.9%) had increased serum creatinine (Table 1 ). At Wk 8 of rescue therapy, 11 (50.0%) pts achieved confirmed CMV viremia clearance; 6 (27.3%) pts had CMV clearance with symptom control at Wk 8 maintained through Wk 16 (Table 2 ). All 22 pts reported treatment-emergent adverse events (TEAEs; Table 3 ); most common TEAEs of special interest were nausea, vomiting, and diarrhea (54.5%), and taste disturbance (50.0%). Neutropenia and acute kidney injury TEAEs were reported by 0 and 3 pts in the rescue arm, respectively. Table 1. Summary of patients from IAT-randomized group meeting criteria for entry into MBV rescue arm* Table 2. Patients achieving confirmed CMV viremia clearance at end of Wk 8 (end of treatment) or achieving confirmed CMV viremia clearance and symptom control at end of Wk 8 maintained through Wk 16 Table 3. Treatment-emergent adverse events during the on-rescue observation period Conclusion: Rescue arm data show MBV was efficacious for R/R CMV infection in HCT/SOT recipients inadequately responding to IAT with/without intolerance and had a similar safety profile to that reported for pts in the randomized MBV group. Disclosures: Marcus Pereira, MD, Hologic (Scientific Research Study Investigator)Merck (Scientific Research Study Investigator)Takeda (Scientific Research Study Investigator, Advisor or Review Panel member) Carlos Cervera, MD, PhD, Avir Pharma (Consultant, Advisor or Review Panel member)Lilly (Consultant, Advisor or Review Panel member)Merck (Consultant, Advisor or Review Panel member, Research Grant or Support)Sunovion (Consultant, Advisor or Review Panel member)Takeda (Consultant, Advisor or Review Panel member)Veritas Pharma (Consultant, Advisor or Review Panel member) Camille Kotton, MD, Shire/Takeda (Advisor or Review Panel member) Camille Kotton, MD, UpToDate (Individual(s) Involved: Self): I write chapters on zoonoses for UpToDate., Independent Contractor Joseph Sasadeusz, MBBS, PhD, Abbvie (Grant/Research Support, Other Financial or Material Support, Consulting fee: speaker)Gilead (Other Financial or Material Support, Speaker)Merck (Grant/Research Support, Consulting fee: speaker)Takeda (Grant/Research Support) Jingyang Wu, MS, Shire Human Genetic Therapies, Inc., a Takeda company (Employee, Other Financial or Material Support, Holds stock/stock options) Martha Fournier, MD, Shire Human Genetic Therapies, Inc., a Takeda company (Employee, Other Financial or Material Support, Holds stock/stock options)Shire ViroPharma, a Takeda company (Other Financial or Material Support, This study was funded by Shire ViroPharma, a Takeda company)